Optimization of Air Distribution in a Baghouse Filter Using Computational Fluid Dynamics - Lima, W. F.; Huebner, R. (Engineering, Technology & Applied Science Research, 2019)
Baghouse filters are used to reduce the emission of pollutants in the atmosphere. With the stricter environmental regulations and the need to avoid the emission of pollutants into the atmosphere, the demand for better results in terms of collection efficiency and filtration rises. A good performance of a baghouse filter is closely linked to the correct flow distribution inside it, whether in the hopper or in the bags. Other important variables for good performance are internal speed, filtration rate (RAP), pressure drop, cleaning efficiency, etc. The upgrading of existing bag filters to current standards is a major challenge for the industry, generally due to, among other factors, emission regulations and common physical and dimensional constraints of the existing equipment. Computational Fluid Dynamics analysis (CFD) can help deal with this problem because it makes possible to perform several analyzes at a lower cost and with great result accuracy when compared with the traditional approaches. In this work, the analysis of an existing bag filter, which presents serious problems of premature discharging of components due to nonuniformity in the internal distribution of the flow, is performed. This analysis has several steps, among them, documentation survey, field survey, flow and pressure drop measurements (pressure differential between the clean side and the dirty side of the filter) with the aid of CFD, with the objective to raise pressure and velocity and to identify possible dimensional changes to improve flow uniformity.